Faktor Individu, Organisasi, dan Sistem Teknologi terhadap Persepsi Perlindungan Hukum Tenaga Keperawatan dalam Implementasi Dokumentasi Asuhan Keperawatan Elektronik - Uneri Uneri; Sentot Imam Suprapto; Novita Ana Anggraini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of individual, organizational, and technological system factors on the perception of legal protection for nursing staff in the use of electronic nursing care documentation. This research method used a quantitative analytical design with a cross-sectional design and a correlational approach. The results showed that partially, individual factors (t=2.260; p=0.026), organizational factors (t=2.327; p=0.022), and technological systems (t=2.422; p=0.018) significantly influenced perceptions of legal protection. Simultaneously, these three factors contributed 40.9% to the perception of legal protection for nursing staff. This indicates that the safety of the nursing profession is highly dependent on the synergy between individual competence, organizational support, and the reliability of technological systems. In conclusion, improvements to hospital management information systems (SIMRS), strengthening standard operating procedures (SOPs), and ongoing training are needed to ensure patient safety and legal protection for nursing staff in the digital era. Keywords: Electronic Documentation, Individual Factors, Organization, Legal Protection, Technological Systems